Biomechanical analysis of the shoulder of swimmers after a maximal effort test. (March 2018) - Serenza, Felipe S.; Oliveira, Anamaria S.; Bedo, Bruno L.S.; Mariano, Fàbio P.; Aquino, Rodrigo; Warner, Martin; Santiago, Paulo R.P.
Abstract: Objectives: To compare the kinematics and electromyography of the periscapular muscles in swimmers before and after a 3-min maximal effort test. Participants: 16 competitive swimmers. Main outcome measurements: Infrared cameras were used to record kinematics in the scapular plane in synchronization with the electromyography system. Results: There was an increase in internal rotation in all angles (p < 0.05), an increase of the anterior tilt, with 120° of elevation (p = 0.04). The serratus anterior showed a decrease in the intervals of 120-90° and 60-30° (p = 0.04; p = 0.02). There was a linear relationship between the variation before and after the maximal effort of the anterior tilt in relation to the variation of muscular activation of the transverse trapezius (p = 0.01) and the lower trapezius (42%, p = 0.01); an internal rotation in 120° and 90° of elevation in relation to the transverse trapezius (p = 0.01); and an internal rotation in 60° and 30° of elevation in relation to the serratus anterior (p = 0.04, p = 0.03). Conclusion: A maximal 3-min effort test resulted in altered scapular biomechanics. More studies are needed to verify if the changes correspond to a risk factor for injuries. Highlights: Increase in internal rotation of the scapula after the test. Increase of the anterior tilt of the scapula with 120° of elevation after the test. The serratus anterior showed a decrease in the muscular activation after the test.